Contribuições para o controle de moscas-das-frutas (Diptera: Tephritidae) - Silva, Joálisson Gonçalves da (2018)
Fruit flies (Diptera: Tephritidae) are phytophagous insects with species that can assume the status of pest in fruit. In Brazil, studies have indicated variations in the diversity of fruit flies, population dynamics and in the interactions with hosts and parasitoids, being fundamental information for an effective control. However, in the Northeast, especially in the state of Paraíba, information on the bioecology of these tefritídeos is scarce. The objective of this study was to characterize the populations of fruit flies in the Brejo Paraibano region through faunal indexes and to evaluate the effect of the use of biodegradable coating on the control and quality of 'Paluma' guava fruits. The research was developed in the Brejo region of Paraiba, covering two rural properties in each municipality, georeferenced and identified according to the criterion of diversity of fruit species, using Invertebrate Zoology laboratories and Post Harvest Physiology Laboratory. The work was developed, addressing the aspects explained above, being divided into four articles. In article I, we studied the faunistic analysis of the community of fruit flies and the similarity between these populations in the municipalities. The population survey was carried out from July 2015 to June 2016. A total of 3,159 fruit flies were captured, of which 85.57% belonged to the genus Anastrepha and 14.43% to the genus Ceratitis. 11 species of fruit flies were caught in the traps. The municipalities studied showed similarity of 54%, which indicates high similarity between the areas. In article II, we aimed to obtain information about the host of fruit flies, their parasitoids and their relationships (parasitoid / fruit fly / host), aiming at the elaboration of future systems of integrated management of these tefritídeos. The botanical species identified as host of fruit flies, belonged to six families and eight fruit species, presenting a richness of 11 species. The diversity of hosts and the availability of fruits are determinant factors for the types of associations between the species of tefritídeos. In article III, the research had as objective to evaluate the population fluctuation of fruit flies and to correlate this information with the phenology of the culture as well as the meteorological elements. In all months of the year infestation of fruit flies was observed for both genera, however the genus Anastrepha excelled in relation to the genus Ceratitis. The MAD index in some municipalities was higher than 0.5 and it is recommended to control the fruit flies in these areas. In article IV, the objective was to evaluate the effect of the use of biodegradable coating associated to different temperature on x the control and quality of guava fruit 'Paluma' infested by C. capitata. The use of biodegradable coatings associated with low temperatures promoted a lethal effect on eggs and larvae of C. capitata, reducing damage and larval survival in infested fruits, preserving the quality and appearance of the fruits and prolonging shelf life.